A best practice framework to measure spatial variation in alcohol availability. (March 2020) - Fry, Richard; Orford, Scott; Rodgers, Sarah; Morgan, Jennifer; Fone, David
Alcohol outlet density and alcohol-related harms are an internationally reported phenomenon. There are multiple methods described in the literature to measure alcohol outlet density, but with very little commentary on the geographical underpinnings of the methods. In this paper, we present a framework to help practitioners and researchers choose the most appropriate spatial method of measuring alcohol outlet density. The framework includes components on theoretical geography, statistical implications and practical considerations, with an emphasis on population-level exposure. We describe the CHALICE alcohol outlet density measurement method that was developed to investigate the relationships between alcohol outlet density and population harm. The CHALICE method is compared to four other methods found in the published literature. We demonstrate the impact of methodological choices (e.g. network vs. Euclidean distances) on resulting alcohol outlet density scores. We conclude that wherever possible the best practice approach to modelling alcohol outlet density should be used to facilitate flexibility in subsequent statistical analysis and improve the transparency of the results.